A baby sister for Frances - Hoban, Russell; Hoban, Lillian (New York : HarperCollins, 1992)
When things change around the house after her baby sister is born, Frances decides to run away--but not too far.
3.2
K-3
Keywords: Babies -- Fiction; Badgers -- Fiction; Family life -- Fiction; Sisters -- Fiction; Badgers -- Fiction; Family life -- Fiction; Infants -- Fiction; Siblings -- Fiction